THE INFLUENCE OF DIGITAL MARKETING, HALAL LABELING AND BUSINESS CAPITAL ON FRANCHISE MSME REVENUE - syafrul, syafrul antoni; rani, rani puspita sari (Universitas Lancang Kuning, 2025)
Abstract: This study aims to analyze the influence of digital marketing, halal labeling, and capital on the income of franchise Micro, Small, and Medium Enterprises (MSMEs). In the digital era, marketing through online platforms is increasingly important for MSMEs to reach a wider range of consumers. In addition, halal labels are an important factor, especially in markets with a majority Muslim consumer, which can influence trust and purchasing decisions. Capital is also an important variable in supporting business operations and development. The research method in this study is quantitative. Using primary data derived from the results of questionnaire answers distributed by researchers to franchise MSME actors in Sungai TFull City. The research sample uses the slovin formula with a sample of 30 MSME actors. This study found that Digital Marketing had an effect on the development of franchise MSMEs in Suangai TFull City, while halal labeling and business capital did not have a significant effect on the income of franchise MSMEs in Sungai TFull City. In conclusion, franchise MSMEs who want to increase their income are advised to optimize their digital marketing strategies and pay attention to the aspect of halal labeling, in addition to managing capital effectively. Keywords: Digital marketing, Halal labeling, Business Capital, Revenue, MSME Franchise.